KESIAPAN BERSEKOLAH ANAK TAMAN KANAK-KANAK KELOMPOK B DITINJAU DARI LEMBAGA PENDIDIKAN DAN TINGKAT PENDIDIKAN ORANG TUA - Srinahyanti Srinahyanti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This research is motivated by the importance of school readiness as the basis for children to learn and achieve achievement in elementary school. Approach and method used in this research is quantitative approach with non-experimental method of comparative with research sample of kindergarten children class B in Sukasari sub-district of Bandung city as many as 100 children. The school readiness measurement tool used in this study is Nijmeegse School bekwaam heids Test (N.S.T.). The analysis of the data is done quantitatively by means of the mean, whitney u test and cruciate test of willis. From the results of N.S.T test shows that 76% of the sample of children declared mature and ready to enter further education (SD) but there are some aspects that need to be developed that is the ability of sharpness of observation and self-knowledge and limbs. Keywords: School Readiness, Kindergarten, Kindergarten Status, Level of Parent Education.